2016
DOI: 10.2337/db15-1193
|View full text |Cite
|
Sign up to set email alerts
|

The Acute-Phase Protein Orosomucoid Regulates Food Intake and Energy Homeostasis via Leptin Receptor Signaling Pathway

Abstract: The acute-phase protein orosomucoid (ORM) exhibits a variety of activities in vitro and in vivo, notably modulation of immunity and transportation of drugs. We found in this study that mice lacking ORM1 displayed aberrant energy homeostasis characterized by increased body weight and fat mass. Further investigation found that ORM, predominantly ORM1, is significantly elevated in sera, liver, and adipose tissues from the mice with high-fat diet (HFD)-induced obesity and db/db mice that develop obesity spontaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 53 publications
1
71
0
Order By: Relevance
“…We specifically examined the acute‐phase proteins pentraxin 2/APCS, which in mice serves an analogous role to C‐reactive protein in humans, and Orm1, which has recently been shown to have anorexigenic properties 18, 27, 28. In males, KPC induced a 34.42 ± 6.89‐fold increase in Apcs ( P  < 0.001, n  = 4–5 per group) and a 6.61 ± 0.32‐fold increase in Orm1 relative to controls ( P  < 0.001, n  = 4–5 per group) ( Figure 7A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We specifically examined the acute‐phase proteins pentraxin 2/APCS, which in mice serves an analogous role to C‐reactive protein in humans, and Orm1, which has recently been shown to have anorexigenic properties 18, 27, 28. In males, KPC induced a 34.42 ± 6.89‐fold increase in Apcs ( P  < 0.001, n  = 4–5 per group) and a 6.61 ± 0.32‐fold increase in Orm1 relative to controls ( P  < 0.001, n  = 4–5 per group) ( Figure 7A).…”
Section: Resultsmentioning
confidence: 99%
“…We also found that KPC increases hepatic expression of Orm1 , another key acute‐phase reactant in both mouse and human known to serve numerous important roles in energy balance, immunity, and capillary barrier modulation. Furthermore, ORM1 is of metabolic and behavioural importance because it induces anorexia via leptin receptor signalling in the arcuate nucleus of the hypothalamus 18. In mice, ORM1 is primarily synthesized by the liver and is the only ORM isoform induced in response to inflammatory stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…() suggest the inability of endothelial cells to transport the hormone across the blood‐brain barrier. Mutated leptin receptors have been observed in obese mice (Sun et al., ). It is unclear what the mechanism behind leptin resistance in this study was.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased leptin levels in cerebrospinal fluid compared to circulation as shown by Caro et al (1996) suggest the inability of endothelial cells to transport the hormone across the blood-brain barrier. Mutated leptin receptors have been observed in obese mice (Sun et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…There can be different causes for disorders in leptin physiological function. Study of mutations and polymorphisms of leptin and leptin receptor genes in the humane and animal models proved the relationship of this protein with obesity (9).…”
Section: Introductionmentioning
confidence: 99%